Unraveling the Mystery of Cancer by Secretory microRNA: Horizontal microRNA Transfer between Living Cells - Kosaka, Nobuyoshi; Ochiya, Takahiro (Frontiers in Genetics, 2012)
microRNAs (miRNAs) have been identified as a fine-tuner in a wide array of biological processes, including development, organogenesis, metabolism, and homeostasis. Deregulation of miRNA leads to the disease status, especially cancer. This occurs through a variety of mechanisms, such as genetic alterations, epigenetic regulation, or altered expression of transcription factors, which target miRNAs. Recently, it was discovered that extracellular miRNAs circulate in the blood of both healthy and diseased patients. Most of the circulating miRNAs are included in RNA-binding proteins, apoptotic bodies, microvesicles, and exosomes. However, the secretory mechanism and biological function, as well as the meaning of the existence of extracellular miRNAs, remain largely unclear. In this article, we summarize the latest and most significant discoveries of original research on secretory miRNA involvement in many aspects of physiological and pathological conditions, with a special focus on cancer. In addition, we discuss a new aspect of cancer research that is revealed by the emergence of “secretory miRNA.”